Implementation of Game-Based Learning in Socialization to Teachers and Students as an Effort to Transform Digital Education - Jonris Tampubolon; Desta Gloria Siahaan; Fitra Ramadhan; Lukas Pardosi; Eliyah Acantha Manapa Sampetoding (English Lecturers and Teachers Association (ELTA), 2026)
This community service activity is driven by the importance of adapting learning methods in line with technological developments and the needs and conditions of students and teachers. The purpose of this community service activity is to provide socialization on the benefits of implementing game-based learning methods by utilizing digital platforms in the modern education era. This activity involved 90 participants consisting of 45 teachers and 45 students of SMAN 1 Kefamenanu, North Central Timor, East Nusa Tenggara. The activity was carried out in September 2025. Before socialization, a pre-test was administered, followed by a post-test and questionnaire distribution to get participants’ feedbacks. The results of the implementation of this socialization activity showed that there was a change in the increase in teacher and student understanding reaching 20% ​​about gamification-based learning and its benefits in increasing learning motivation. However, in supporting the implementation of gamification-based learning, good cooperation is needed between teachers and school administrators in providing the necessary supporting facilities for the learning process. Keywords : Game-Based Learning; Socialization; Digital Education; Learning Motivation